Confirmatory Factor Analysis on the Measurement of Parental Guidance Scale in Reading - Helena Magdalena; Desvi Yanti Mukhtar; Ika Sari Dewi (Pusdikra Publishing, 2026)
This study aimed to develop and validate the Parent Tutoring in Reading scale as an instrument to measure parental involvement in supporting children’s reading at home. This study used a quantitative instrument development design. The scale was constructed based on four dimensions of parent tutoring: parental involvement; motivation and time provided; perception of competencies and resources; and quality of support and communication. Content validity was evaluated by a panel of six experts, followed by a readability test and field testing. The participants were 262 parents of lower-grade elementary school students, consisting of 213 females and 49 males, selected through purposive nonprobability sampling. Construct validity was examined using Confirmatory Factor Analysis (CFA) in JASP, while reliability was assessed using Cronbach’s alpha. The results showed that all items met the content validity criteria and demonstrated acceptable expert agreement. After empirical testing, 2 items were removed, leaving 33 items retained as valid. The CFA results indicated an acceptable overall model fit, with SRMR = 0.042, GFI = 0.998, CFI = 0.987, TLI = 0.986, and RMSEA = 0.086. In addition, the scale demonstrated excellent internal consistency, with a Cronbach’s alpha coefficient of 0.985. These findings indicate that the Parent Tutoring in Reading scale is a valid and reliable instrument for assessing parent tutoring practices in reading contexts in Indonesia.